Kajian Mekanisme Corporate Governance Terhadap Integritas Laporan Keuangan - Raden Roro Sekar Hayuningrum; Shinta Permata Sari (ITB AAS INDONESIA, 2023)
Financial reports must show great integrity to help their users make good decisions. The financial statements have integrity if the information in its contain describe the company's actual financial transactions. Without integrity, financial reporting will create mistrust of the company's management and reduce the company's public image. This study aims to determine the effect of corporate governance mechanisms on the integrity of financial reports. The corporate governance mechanism in this study is proxied by institutional ownership, managerial ownership, independent commissioners, and audit committees. The sample for this research is a food and beverage industry classification company listed on the Indonesia Stock Exchange in 2019–2021, which is determined using a purposive sampling method. The data analysis method used in this study is multiple linear regression. The results of the study show that institutional ownership, independent commissioners, and audit committees have an effect on the integrity of financial statements. Meanwhile, managerial ownership has no effect on the integrity of financial reports.